Prevalence of multidrug-resistant Escherichia coli isolates and virulence gene expression in poultry farms in Jos, Nigeria - Agusi, Ebere Roseann; Kabantiyok, Dennis; Mkpuma, Nicodemus; Atai, Rebecca Bitiyong; Okongwu-Ejike, Chidinma; Bakare, Ebun Lydia; Budaye, James; Sule, Kabiru Garba; Rindaps, Rindah Joy; James, Gyallak Kingsley; Audu, Benshak John; Agada, Godwin Ojonugwa; et al. (Frontiers in Microbiology, 2024)
Introduction Antimicrobial resistance is increasingly becoming a global health concern. This study aimed to investigate and report MDR Escherichia coli (E. coli) prevalence, resistance, and virulence genes from poultry in Jos, Plateau State, Nigeria. Methods The samples were analyzed using microbiological standard methods and polymerase chain reactions (PCRs). Results A total of 179 cloacal swabs were collected from bothlocal and exotic poultry breeds, of which 99.4% (178/179) tested positive for E. coli. Among these culturally identified samples, 99.4% (177/178) were furtherconfirmed Escherichia coli with a molecular weight of 401 bp. Multidrugresistance of 45% (80/178) was observed from the confirmed isolates. PCR assays were conducted to detect genes associated with resistance to antibiotics, specifically, tetracycline (tetA gene), sulfonamide (sul1 gene), ampicillin (ampC gene), and quinolone (gyrA gene). Antimicrobial susceptibility test (AST) results revealed substantial antibiotic resistance, with 81.9% (145/177) of the isolates being resistant to tetracycline, 80.2% (142/177) to quinolone, 69.5% (123/177) to sulfonamide, and 66.1% (117/177) to ampicillin. Further analysis on 18 isolates that showed resistance to up to four different antibiotics was carried out using multiplex PCR to detect eae, hlyA, rfbE, fliC, and fstx virulence genes. The study found that 44.4% (15/18) of the isolates were positive for the eae gene, 27.7% (5/18) for stx, 22.2% (4/18) for rfbe gene, and 5.5% (1) for hlya gene, and none tested positive for fliC gene. Conclusion These results showed high antibiotic resistance, virulent genes, and significant levels of MDR in E. coli from poultry. This study highlights the urgent need for antimicrobial stewardship practices within the poultry industry due to their profound implications for food safety and public health. This issue is particularly critical in Nigeria, where poultry farming constitutes a significant portion of smallholder farming practices.